Estimation of Economic Growth in France Using Business Survey Data - Kabundi, Alain (IMF Working Papers; Working Paper, 2004)
This paper proposes a new way of computing a coincident indicator for economic activity in France using data from business surveys. We use the generalized dynamic factor model a la Forni and others (2000) to extract common components from a large number of survey observations. The results obtained show that the resulting indicator forecasts economic activity with a relatively high degree of accuracy before the release of actual data.